2020
DOI: 10.1097/sla.0000000000004251
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year Evaluation of a Large Retrospective Cohort Treated by Sacral Nerve Modulation for Fecal Incontinence

Abstract: Objective:The aim of this study was to assess the effectiveness of sacral nerve modulation (SNM) in a large cohort of patients implanted for at least 10 years, quantify adverse event rates, and identify predictive factors of long-term success.Summary Background Data:Few studies have evaluated the long-term success of SNM.Methods:Data collected prospectively from patients implanted for fecal incontinence (FI) in 7 French centers between January 1998 and December 2008 were retrospectively analyzed. Patient FI se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
(88 reference statements)
0
8
0
2
Order By: Relevance
“…Given the difficulties in obtaining FI severity and quality scores and/or bowel diaries over a long follow‐up period, the outcome of SNM was defined as favourable if the patient reported a therapeutic benefit from SNM and did not consider discontinuation or additional therapy beyond the use of medications to modify bowel transit. Treatment outcome was defined as unfavourable if the patient was not satisfied with SNM and required an alternative treatment (medical treatment excluded) such as stoma formation or trans‐anal irrigation or if the patient had switched off the IPG or had had it surgically removed [14].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the difficulties in obtaining FI severity and quality scores and/or bowel diaries over a long follow‐up period, the outcome of SNM was defined as favourable if the patient reported a therapeutic benefit from SNM and did not consider discontinuation or additional therapy beyond the use of medications to modify bowel transit. Treatment outcome was defined as unfavourable if the patient was not satisfied with SNM and required an alternative treatment (medical treatment excluded) such as stoma formation or trans‐anal irrigation or if the patient had switched off the IPG or had had it surgically removed [14].…”
Section: Methodsmentioning
confidence: 99%
“…Data are expressed as means ± standard deviation (SD) or as median (interquartile range) if nonnormally distributed. The proportion of patients in each outcome was determined for both the intention to treat (ITT) approach and the per protocol (PP) approach [14]. For quantitative endpoints, Student’s t ‐test or the Mann–Whitney test, as appropriate, was used to compare groups.…”
Section: Methodsmentioning
confidence: 99%
“…These are activated by sacral nerve stimulation, an increasingly used, front-line treatment for faecal incontinence. 35 Intestinofugal neurons are a peculiar class of enteric neurons with cell bodies in the myenteric ganglia with their axons projecting out of the gut to synapse with sympathetic neurons in prevertebral ganglia. In several laboratory animals these pathways mediate intestino-intestinal inhibitory reflexes.…”
Section: Cellular Morphology Of Enteric Neuronesmentioning
confidence: 99%
“…From here, their effects are mediated by postganglionic nerve fibres to the pelvic organs. These are activated by sacral nerve stimulation, an increasingly used, front‐line treatment for faecal incontinence 35 …”
Section: Structure Of the Enteric Nervous Systemmentioning
confidence: 99%
“…The treatment is effective in the long-term [intention-to-treat 54% over a median of 56 months follow up ( Thin et al, 2013 )], with complete continence achieved in about one third of patients ( Altomare et al, 2015 ). A recent retrospective study showed that efficacy is maintained in 45% of patients at 10 years post-implantation ( Desprez et al, 2020 ). Whilst some evidence has been provided by small double-blind crossover studies, randomized data are lacking, and experimental efficacy has not yet been validated in an adequately powered clinical trial ( Thaha et al, 2015 ; McAlees et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%